Composite member, bonded body, and holding device
The composite member with controlled distribution of aluminum nitride, silicon carbide, and titanium compound addresses thermal conductivity issues by ensuring uniform heat conduction and managing thermal expansion, achieving high thermal conductivity and efficient heat dissipation.
Patent Information
- Application Number
- JP2023102158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-22
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-06-22
AI Technical Summary
Existing composite members experience low thermal conductivity due to gaps acting as heat transfer resistance and variations in particle distribution, leading to non-uniform heat conduction.
A composite member composed of aluminum nitride and silicon carbide with controlled distribution maps of silicon, carbon, and aluminum, ensuring regions of high thermal conductivity materials are uniformly distributed, and a titanium compound is included to manage thermal expansion.
The composite member achieves thermal conductivity of 80 W/(m·K) or more, ensuring uniform heat transmission and preventing damage from thermal expansion, enhancing heat dissipation efficiency.
Smart Images

Figure 2025002179000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite member, a joint, and a holding device. [Background technology]
[0002] Composite members made of multiple materials have been known for some time. For example, Patent Documents 1 and 2 disclose composite members having silicon carbide as a main constituent phase and including titanium silicide, titanium silicon carbide, etc. Patent Document 3 discloses a composite member having titanium silicide as a main constituent phase and including silicon carbide, titanium carbide, etc. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 6182082 [Patent Document 2] Patent No. 5666748 [Patent Document 3] Patent Publication No. 2021-116218 Summary of the Invention [Problem to be solved by the invention]
[0004] However, even with the prior art such as Patent Documents 1 to 3, there is still room for improvement in the technology for improving the thermal conductivity of a composite member. For example, the composite members described in Patent Documents 1 and 2 contain silicon carbide particles, and the composite member described in Patent Document 3 contains titanium silicide particles. For this reason, gaps that become heat transfer resistance are easily formed between the particles inside the composite member, and the thermal conductivity varies depending on the dispersion state of the particles. Therefore, there is a risk that the thermal conductivity of the composite member will be reduced.
[0005] An object of the present invention is to provide a technique for improving thermal conductivity in a composite material. [Means for solving the problem]
[0006] The present invention has been made to solve at least part of the above-mentioned problems, and can be realized in the following forms.
[0007] (1) According to one embodiment of the present invention, there is provided a composite member comprising aluminum nitride and silicon carbide, and when a silicon distribution map, a carbon distribution map and an aluminum distribution map are superimposed on each other in a cross section of the composite member obtained by energy dispersive X-ray spectroscopy (EDS), the silicon distribution region has a region where silicon and carbon overlap and a region where silicon and carbon do not overlap, and inside the region where silicon and carbon do not overlap, there is a region where silicon and aluminum overlap.
[0008] According to this configuration, when the silicon distribution map, the carbon distribution map, and the aluminum distribution map are superimposed on each other in the cross section of the composite member obtained by the EDS method, the composite member has a region where silicon and carbon overlap and a region where silicon and carbon do not overlap in the silicon distribution region. That is, silicon carbide with relatively high thermal conductivity is unevenly distributed. On the other hand, inside the region where silicon and carbon do not overlap, there is a region where silicon and aluminum overlap. That is, aluminum nitride with relatively high thermal conductivity is present in the region where silicon carbide does not exist. As a result, either silicon carbide or aluminum nitride with relatively high thermal conductivity is present in the entire composite member, so that the variation in thermal conductivity in the composite member can be reduced and the thermal conductivity can be improved.
[0009] (2) In the composite member of the above embodiment, the composite material may contain a titanium compound. According to this configuration, since the composite member contains a titanium compound, it is possible to control the thermal expansion coefficient of the composite member formed from aluminum nitride and silicon carbide. As a result, when the composite member is bonded to another member that becomes high temperature and used as a heat dissipation member, for example, it is possible to suppress the other member from peeling off from the composite member due to the difference in thermal expansion. As a result, the composite member can efficiently release (extract) heat from the other member and maintain a bonded state with the other member.
[0010] (3) In the composite material of the above embodiment, the thermal conductivity may be 80 W / (m K) or more. According to this configuration, aluminum nitride having a relatively small grain size is contained in an area inside the composite material where silicon carbide is not present. This allows the thermal conductivity of the entire composite material to be 80 W / (m K) or more.
[0011] (4) According to another aspect of the present invention, a joined body is provided. The joined body includes the above-mentioned composite member and a ceramic material joined to the composite member. According to this configuration, the joined body includes a composite member that easily transfers heat and a ceramic material joined to the composite member. This allows the heat of the ceramic material to be efficiently released via the composite member, thereby suppressing damage to the joined body due to heat.
[0012] (5) In the joined body of the above embodiment, the composite member and the ceramic material may be joined by metal joining. According to this configuration, the composite member and the ceramic material are joined by metal joining, which is relatively easy to transfer heat. As a result, the heat of the ceramic material is relatively easily transferred to the composite member, so that the heat of the ceramic material can be more efficiently released through the composite member. Therefore, damage to the joined body due to heat can be suppressed.
[0013] (6) According to yet another aspect of the present invention, there is provided a holding device. This holding device includes the above-described joined body, the ceramic material has a chuck electrode, and the composite member has a cooling function. According to this configuration, the holding device can hold an object using the chuck electrode of the ceramic material. At this time, heat from the ceramic material is transferred to the composite member, which is a good conductor of heat, and can be released to the outside of the joined body by the cooling function of the composite member. This makes it possible to suppress damage to the holding device due to heat.
[0014] The present invention can be realized in various forms, for example, in the form of a method for manufacturing a composite member and a joined body, an apparatus including a composite member and a joined body, a system including a holding device, and a method for controlling these apparatus and systems. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a perspective view of the retaining device according to the first embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of the holding device of the first embodiment. [Diagram 3] FIG. 2 is a first diagram illustrating a cross section of a composite material. [Figure 4] FIG. 2 is a second diagram illustrating a cross section of a composite member. [Diagram 5] FIG. 3 is a third diagram illustrating a cross section of a composite member. [Figure 6] FIG. 2 is a diagram for explaining the mixing ratio of raw materials in samples used in an evaluation test. [Figure 7] FIG. 13 is a diagram illustrating the results of an evaluation test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] First Embodiment FIG. 1 is a perspective view of a holding device 100 of the first embodiment. FIG. 2 is a cross section of the holding device 100 of the first embodiment. The holding device 100 of the first embodiment is, for example, an electrostatic chuck that holds a wafer W by electrostatic attraction, and is provided in an etching device or the like. The holding device 100 includes a bonded body 1 having a ceramic material 10, a composite member 20, and a bonding portion 30. In the bonded body 1, as shown in FIG. 1, the ceramic material 10, the bonding portion 30, and the composite member 20 are laminated in this order from the positive side in the z-axis direction (lamination direction). In this embodiment, the bonded body 1 is a columnar body having a substantially circular cross section perpendicular to the lamination direction. Note that each figure shows the arrangement of each part in a schematic manner, and does not accurately show the ratio of the dimensions of each part.
[0017] The ceramic material 10 is a substantially circular flat plate member made of alumina (Al2O3). The ceramic material 10 has a pair of main surfaces 10a, 10b (see FIG. 2). One of the pair of main surfaces 10a, 10b, the main surface 10a, is formed with a mounting surface on which a wafer W is mounted. The wafer W mounted on the mounting surface is attracted and fixed to the mounting surface by electrostatic attraction generated by a chuck electrode 11 disposed inside the ceramic material 10. A heater electrode (not shown) for heating the wafer W attracted and fixed to the mounting surface may be built into the ceramic material 10. The material forming the ceramic material 10 may be aluminum nitride (AlN), zirconia (ZrO2), silicon nitride (Si3N4), silicon carbide (SiC), yttria (Y2O3), or the like.
[0018] The composite member 20 contains aluminum nitride (AlN), silicon carbide (SiC), and a titanium compound. The composite member 20 of this embodiment contains TiSi2 and Ti3SiC2 as titanium compounds. The ease of thermal expansion of the composite member 20 is determined by the ease of thermal expansion of the titanium compound. Therefore, by including a titanium compound, it is possible to adjust the degree of thermal expansion of the composite member 20. In this embodiment, the difference between the thermal expansion coefficient of the composite member 20 and the thermal expansion coefficient of the ceramic material 10 is 0.3×10 -6 / K or less. The thermal conductivity of the composite material 20 is 80 W / (m·K) or more. As shown in Fig. 2, the composite material 20 has a plurality of refrigerant flow paths 21 through which a refrigerant flows. The composite material 20 will be described in detail later.
[0019] The joint 30 is disposed between the other of the pair of main surfaces 10a, 10b of the ceramic material 10 and the composite member 20. The joint 30 joins the ceramic material 10 and the composite member 20. In this embodiment, the joint 30 is a metal compound made of Al-Mg. This allows heat to be easily transferred between the ceramic material 10 and the composite member 20.
[0020] Next, a method for manufacturing the holding device 100 will be described. In manufacturing the holding device 100, first, the ceramic material 10 and the composite member 20 are each manufactured. For the ceramic material 10, a plurality of green sheets are manufactured using a slurry containing alumina powder. The manufactured green sheets are stacked while sandwiching a heater electrode therebetween to manufacture a roughly circular plate-shaped molded body with a heater electrode built in therein. The manufactured molded body is fired under predetermined conditions to complete the ceramic material 10. The ceramic material 10 may also be manufactured by a press molding method.
[0021] Composite material 20 is prepared by weighing out the following quantities of silicon carbide powder (average particle size 15.5 μm), silicon powder (average particle size 10.12 μm), titanium powder (average particle size 27 μm), and aluminum nitride powder (median 15 μm). Silicon carbide: 15.0% by mass Silicon: 16.4% by mass Titanium: 38.8% by mass Aluminum nitride: 29.8% by mass
[0022] In the manufacture of the composite member 20 of this embodiment, a plurality of green sheets are manufactured using a slurry prepared by mixing the weighed powders. The manufactured green sheets are stacked to manufacture a molded body having a space therein that serves as a refrigerant flow path. The manufactured molded body is fired under predetermined conditions (firing temperature: 1400°C, firing time: 4 hours, firing atmosphere: vacuum atmosphere) to complete the composite member 20. Finally, the ceramic material 10 and the composite member 20 are bonded with a metal compound made of Al-Mg to complete the holding device 100. The composite member 20 may be manufactured by a press molding method.
[0023] FIG. 3 is a first diagram for explaining a cross section of the composite material 20 of the first embodiment. FIG. 3 is a diagram that shows a schematic cross section of the composite material 20, which is imaged using a scanning electron microscope (SEM). The cross section shown in FIG. 3 shows a region where silicon exists (region R1 shown by hatching with closely spaced dots), a region where titanium exists (region R2 shown by hatching with widely spaced dots), a region where aluminum nitride exists (region R3 shown by hatching with dashed dotted lines), and a region where silicon carbide exists (region R4 shown by hatching with multiple horizontal lines). In the cross section of the composite material 20, the region where silicon exists, the region where titanium exists, the region where aluminum nitride exists, and the region where silicon carbide exists are distinguished by comparing the cross section shown in FIG. 3 with the results of energy dispersive X-ray diffraction method for the same cross section.
[0024] In FIG. 3, regions R1 and R2 contain titanium silicide (TiSi2) and titanium silicon carbide (Ti3SiC2) produced by the reaction between silicon carbide and titanium used as raw materials. In the cross section of the composite member 20, aluminum nitride (region R3) is classified into aluminum nitride particles Pa1 having a particle size of 2 μm or more, centered on aluminum nitride particles having a particle size of about 15 μm, which is the particle size of the aluminum nitride particles used as raw materials, and aluminum nitride lumps Pa2 having a size smaller than 2 μm. As shown in FIG. 3, the aluminum nitride lumps Pa2 are dispersed in the region R1 where silicon exists (see region A1 surrounded by a dotted line in FIG. 3). In the composite member 20 of this embodiment, by using aluminum nitride powder as a raw material in a range of 15 mass % to 50 mass % when producing the composite member 20, it becomes easier to include lumps Pa2 whose size is smaller than the particle size of the raw material.
[0025] FIG. 4 is a second diagram illustrating the cross section of the composite member 20 of this embodiment. In FIG. 4, the distribution diagrams of silicon, carbon, and aluminum obtained when the cross section of the composite member 20 is analyzed by energy dispersive X-ray spectroscopy are shown in separate diagrams. The three diagrams shown in FIG. 4 are schematic diagrams of element distribution obtained by energy dispersive X-ray spectroscopy at the same position, and show the part where the X-ray intensity specific to each atom is equal to or higher than a certain level. From FIG. 4, it is expected that the carbon distribution region Dc partially overlaps with the silicon distribution region Ds. In the aluminum element distribution shown in FIG. 4, aluminum nitride particles Pa1 having a particle size of about 15 μm and aluminum nitride chunks Pa2 having a size of about 1 μm, which were also explained in FIG. 3, are shown.
[0026] FIG. 5 is a third diagram for explaining the cross section of the composite member 20 of the present embodiment. FIG. 5 shows a silicon distribution map, a carbon distribution map, and an aluminum distribution map superimposed on each other in the cross section of the composite member 20 shown in FIG. 4. As shown in FIG. 5, when the silicon distribution map, the carbon distribution map, and the aluminum distribution map are superimposed on each other in the cross section of the composite member 20 obtained by energy dispersive X-ray spectroscopy, the composite member 20 has a region Dsc1 where silicon and carbon overlap and a region Dsc0 where silicon and carbon do not overlap in the silicon distribution region Ds, and has a region Dsa1 where silicon and aluminum overlap inside the region Dsc0 where silicon and carbon do not overlap (the region Dsc1 and the region Dsc0 are each surrounded by a thick solid line in FIG. 5). The region Dsa1 where silicon and aluminum overlap corresponds to the aluminum nitride lump Pa2 whose size is smaller than 2 μm shown in FIG. 3. The region Dsa1 where silicon and aluminum overlap is presumably formed when a solid solution is formed between the raw material particles of silicon carbide and aluminum nitride during firing in the production of the composite member 20, and part of the molten aluminum nitride penetrates into the silicon carbide structure. In the composite member 20 of this embodiment, as shown in Fig. 5, when the silicon distribution region Ds is viewed by scanning electron microscopy (SEM), the area of the region Dsa1 where silicon and aluminum overlap is smaller than the area of the region Dsc1 where silicon and carbon overlap.
[0027] Next, an evaluation test of the composite material will be described. In this evaluation test, a number of composite materials with different contents of the constituent phases were produced by changing the mixing ratio of the raw materials used in the production of the composite material, and the thermal conductivity of each was evaluated and compared.
[0028] FIG. 6 is a diagram explaining the mixing ratio of the raw materials in the composite member samples used in this evaluation test. First, the method of producing the samples used in this evaluation test will be explained. In this evaluation test, four types of samples were prepared as samples to be evaluated. Each of the four types of samples was produced by molding and firing a mixture of at least three types of raw materials out of the five types of raw materials shown in FIG. 6. For each of the five types of raw materials, particles having the particle sizes shown below were used. SiC: 15.5μm (average particle size) Si:10.12μm (average particle size) Ti:27μm (average particle size) TiSi2: 5~10μm (average particle size) AlN: 15 μm (median)
[0029] As shown in FIG. 6, sample 1 does not use aluminum nitride as a raw material. Samples 2 to 4 have a larger amount of aluminum nitride than silicon carbide as a raw material. As described above, when the amount of aluminum nitride as a raw material is in the range of 15 mass % to 50 mass %, it is easy to contain aluminum nitride chunks smaller than the grain size of the raw material. Samples 2 to 4 all have an aluminum nitride amount of about 30 mass %, and are easy to contain aluminum nitride chunks smaller than the grain size of the raw material in the cross section. Samples 1 to 4 shown in FIG. 6 were produced by firing at a firing temperature of 1400° C. for 4 hours in a vacuum atmosphere.
[0030] Figure 7 is a diagram illustrating the results of this evaluation test. Figure 7 shows the ratio (unit: mass%) of each of the five constituent phases and the thermal conductivity (unit: W / (m K)) for each of Samples 1 to 4. The ratio of each of the five constituent phases contained in Samples 1 to 4 was determined by an X-ray diffraction device (measurement conditions: CuKα, 40 kV, 40 mA, 2θ=5 to 70°) using samples ground in a mortar.
[0031] In this evaluation test, we assumed a composite material to be joined with a ceramic material made of alumina, and evaluated four types of samples based on the thermal conductivity required for joining with alumina. The thermal conductivity of alumina (Al2O3) is generally less than 30 W / (m·K). For this reason, if the sample is to be used as a composite material to be joined with a ceramic material made of alumina, the thermal conductivity of the sample should be 80 W / (m·K) or more, which is more than twice the thermal conductivity of alumina. Hereinafter, the thermal conductivity of 80 W / (m·K) will be referred to as the "reference thermal conductivity." The thermal conductivity of the samples was measured using the laser flash method.
[0032] It was found that Sample 1 contained almost no aluminum nitride as a constituent phase and had a thermal conductivity smaller than the standard thermal conductivity, whereas Samples 2 to 4 contained more aluminum nitride than silicon carbide as a constituent phase and had a thermal conductivity larger than the standard thermal conductivity.
[0033] According to the composite member 20 of the present embodiment described above, when the silicon distribution map, the carbon distribution map, and the aluminum distribution map in the cross section of the composite member 20 obtained by the EDS method are superimposed as shown in FIG. 5, the silicon distribution region Ds has a region Ds1 where silicon and carbon overlap and a region Ds0 where silicon and carbon do not overlap. This means that silicon carbide with relatively high thermal conductivity is unevenly distributed. On the other hand, inside the region Dsc0 where silicon and carbon do not overlap, there is a region Dsa1 where silicon and aluminum overlap. That is, in the composite member 20, a lump of aluminum nitride with relatively high thermal conductivity exists in the region where silicon carbide does not exist. As a result, either silicon carbide or aluminum nitride with relatively high thermal conductivity exists in the entire composite member 20, so that the variation in thermal conduction in the composite member 20 is reduced. Therefore, the thermal conductivity of the composite member 20 can be improved.
[0034] In addition, in general, in a composite member containing a large amount of silicon carbide particles, the distribution of silicon carbide varies within the composite member. Therefore, the thermal conductivity within the composite member becomes non-uniform, and for example, when the composite member is used as a member for transmitting heat, there is a risk that the heat is not transmitted uniformly. In the composite member 20 of this embodiment, in the region where silicon carbide does not exist, a solid solution of silicon carbide and aluminum nitride is formed, and a plurality of aluminum nitride lumps smaller than the particle size of the raw material are formed. As a result, the silicon carbide particles and the aluminum nitride lumps are dispersed in the cross section of the composite member 20, so that the thermal conductivity within the composite member 20 is easily uniform, and the uniformity of the thermal conductivity within the composite member 20 can be improved. Therefore, when the composite member 20 is used as a member for transmitting heat, heat can be transmitted uniformly.
[0035] Furthermore, according to the composite member 20 of this embodiment, the composite member 20 contains a titanium compound, which controls the thermal expansion coefficient of the composite member 20 formed from aluminum nitride and silicon carbide. In the joined body 1, by making the thermal expansion coefficient of the composite member 20 close to that of the ceramic material 10, it is possible to suppress peeling of the ceramic material 10 from the composite member 20 due to the difference in thermal expansion. As a result, the composite member 20 can efficiently release heat from the ceramic material 10, thereby improving the thermal conductivity of the composite member 20 and suppressing damage to the joined body 1.
[0036] Furthermore, composite member 20 of the present embodiment has relatively small aluminum nitride lumps in regions Dsc0 where silicon and carbon do not overlap, i.e., regions where no silicon carbide is present, inside composite member 20. This allows the thermal conductivity of composite member 20 as a whole to be 80 W / (m K) or higher, which is at least twice as high as the thermal conductivity of alumina.
[0037] Moreover, according to the joined body 1 of the present embodiment, the joined body 1 includes the ceramic material 10 joined to the composite member 20 which easily transmits heat. This allows the heat of the ceramic material 10 to be efficiently released through the composite member 20, thereby making it possible to suppress damage to the joined body 1 due to heat.
[0038] Moreover, according to the joined body 1 of the present embodiment, the composite member 20 and the ceramic material 10 are joined at the joint 30 by metal joining, which is a relatively easy-to-transfer heat. This allows the heat of the ceramic material 10 to be transferred relatively easily to the composite member 20, so that the heat of the ceramic material 10 can be released more efficiently via the composite member 20. Therefore, damage to the joined body 1 due to heat can be suppressed.
[0039] The holding device 100 of the present embodiment is an electrostatic chuck, and can hold the wafer W using the chuck electrode 11 of the ceramic material 10. At this time, the heat of the ceramic material 10 is transferred to the composite member 20, which easily transfers heat, and can be released to the outside of the bonded body 1 by the coolant flowing through the coolant flow path 21 of the composite member 20. This can suppress damage to the holding device 100 due to heat.
[0040] <Modifications of this embodiment> The present invention is not limited to the above-described embodiment, and can be embodied in various forms without departing from the spirit and scope of the invention. For example, the following modifications are also possible.
[0041] [Variation 1] In the above-described embodiment, the composite material 20 contains a titanium compound. The composite material does not have to contain a titanium compound, but the thermal expansion coefficient of the composite material can be adjusted by adjusting the content of the titanium compound.
[0042] [Variation 2] In the above-described embodiment, in order to facilitate dissipation of heat from the ceramic material 10 when the joined body 1 is used as an electrostatic chuck, the thermal conductivity of the composite material 20 is set to 80 W / (m K) or more. However, the thermal conductivity of the composite material 20 is not limited to this value.
[0043] [Variation 3] In the above embodiment, the joined body 1 includes the ceramic material 10, the composite member 20, and the joint 30, but the configuration of the joined body 1 is not limited to this. The material forming the member joined to the composite member 20 is not limited to ceramics such as alumina. The joint does not have to be a metal joint. Any configuration that can utilize the high thermal conductivity of the composite member may be used.
[0044] [Variation 4] In the above embodiment, the joined body 1 is used in the holding device 100, but the application field of the joined body 1 is not limited thereto. The joined body 1 can be applied in any field in which the high thermal conductivity of the composite member can be utilized.
[0045] Although the present aspect has been described above based on the embodiment and modified examples, the above-mentioned embodiment of the aspect is intended to facilitate understanding of the present aspect and does not limit the present aspect. The present aspect may be modified or improved without departing from the spirit and scope of the claims, and equivalents are included in the present aspect. Furthermore, if a technical feature is not described as essential in this specification, it may be deleted as appropriate.
[0046] (Application example 1) A composite member, Contains aluminum nitride and silicon carbide, When a silicon distribution map, a carbon distribution map, and an aluminum distribution map in a cross section of the composite member obtained by energy dispersive X-ray spectroscopy (EDS method) are superimposed, The silicon distribution region has a region where silicon and carbon overlap and a region where silicon and carbon do not overlap, The silicon-aluminum alloy has a region where silicon and aluminum overlap inside a region where silicon and carbon do not overlap. A composite member characterized by: (Application example 2) The composite member according to Application Example 1 further comprises: Contains titanium compounds, A composite member characterized by: (Application example 3) The composite member according to Application Example 1 or Application Example 2, Thermal conductivity is 80W / (m K) or more. A composite member characterized by: (Application example 4) A conjugate comprising: A composite member according to any one of Application Examples 1 to 3, and a ceramic material bonded to the composite member. A conjugate characterized in that (Application example 5) The bonded structure according to any one of Application Examples 1 to 4, The composite material and the ceramic material are joined by metal joining. A conjugate characterized in that (Application example 6) A holding device, comprising: The joint body according to any one of Application Examples 1 to 5 is provided, the ceramic material includes a chuck electrode; The composite member has a cooling function. A holding device characterized in that [Explanation of symbols]
[0047] 1...Holding device 10…Ceramic material 11...Chuck electrode 20...Composite material 21... Coolant flow path
Claims
1. A composite member, Contains aluminum nitride and silicon carbide, When a distribution map of silicon, a distribution map of carbon, and a distribution map of aluminum in a cross section of the composite member obtained by energy dispersive X-ray spectroscopy (EDS method) are superimposed, The silicon distribution region has a region where silicon and carbon overlap and a region where silicon and carbon do not overlap, The silicon-aluminum alloy has a region where silicon and aluminum overlap inside a region where silicon and carbon do not overlap. A composite member characterized by:
2. The composite member according to claim 1 further comprises: Contains titanium compounds, A composite member characterized by:
3. The composite member according to claim 1 or 2, The thermal conductivity is 80 W / (m K) or more. A composite member characterized by:
4. A conjugate comprising: A composite material according to claim 1 or 2; and a ceramic material bonded to the composite member. A conjugate characterized in that
5. The joint body according to claim 4, The composite material and the ceramic material are joined by metal joining. A conjugate characterized in that
6. A holding device, comprising: The joint body according to claim 4 is provided, the ceramic material includes a chuck electrode; The composite member has a cooling function. A holding device characterized in that
Citation Information
Patent Citations
Aluminum nitride ceramic composite material and preparation method thereof
CN104402480A
Electrostatic chuck plate and manufacture thereof
JP1987286247A
Heater device
JP2001313157A
Electrostatic chuck
JP2003152062A
Ceramic material and method for producing the same
JP2011219321A
Cited By
Composite member, joint, and holding device
JP7727150B2
Composite member, joined body, and holding device
JPWO2024176903A1